2007
DOI: 10.1002/med.20104
|View full text |Cite
|
Sign up to set email alerts
|

Inosine monophosphate dehydrogenase (IMPDH) as a target in drug discovery

Abstract: Inosine monophosphate dehydrogenase (IMPDH) is a key enzyme of de novo purine nucleotide biosynthesis and is viewed as an important target in the quest for discovery of drugs in the antiviral, antibacterial and anticancer therapeutic areas. This review focuses on the medicinal chemistry, drug discovery and chemical biology of IMPDH. Examples of IMP and cofactor site-directed inhibitors, allosteric inhibitors and isoform-selective inhibitors are presented. Comparison of IMPDHs from different organisms is also m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
95
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(96 citation statements)
references
References 62 publications
0
95
0
1
Order By: Relevance
“…It is interesting to note that of the three orthologues of IMPDH, guaB3 and guaB2 are in an operon, and guaB1 is elsewhere in the genome. The Mt-GuaB orthologues have approximately 41 % sequence identity at the amino acid level with human IMPDH (Shu & Nair, 2008). A genome-wide transposon mutagenesis study has suggested that Mt-GuaB2 is the only essential orthologue for growth of M. tuberculosis H37Rv (Sassetti et al, 2001(Sassetti et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that of the three orthologues of IMPDH, guaB3 and guaB2 are in an operon, and guaB1 is elsewhere in the genome. The Mt-GuaB orthologues have approximately 41 % sequence identity at the amino acid level with human IMPDH (Shu & Nair, 2008). A genome-wide transposon mutagenesis study has suggested that Mt-GuaB2 is the only essential orthologue for growth of M. tuberculosis H37Rv (Sassetti et al, 2001(Sassetti et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to such well-known competitive and uncompetitive IMPDH inhibitors as mycophenolate mofetil, mizoribine and ribavirin with respect to IMP. 8) To elucidate in detail the interaction between IMPDH and curcumin, it will be necessary to examine the X-ray crystal and NMR analyses of the complex of IMPDH and curcumin.…”
mentioning
confidence: 99%
“…1 The activity of IMPDH is correlated with the growth of cells, and IMPDH has become one of the important targets of antiviral, antimicrobial, anti-cancer and immunosuppressive therapy drugs. 2 Several classes of IMPDH inhibitors are now in clinical use or are under development. [3][4][5][6][7] However, some of them suffer from a certain degree of toxicity and/or susceptibility to metabolic inactivation.…”
mentioning
confidence: 99%